2013
DOI: 10.21149/spm.v55i3.7210
|View full text |Cite
|
Sign up to set email alerts
|

Iron, zinc, copper and magnesium deficiencies in Mexican adults from the National Health and Nutrition Survey 2006

Abstract: Objective. To describe the prevalence of serum iron and zinc deficiencies and low serum concentrations (LSC) of copper and magnesium in Mexican adults. Materials and methods. Blood samples from subjects (≥20 years, both genders) participating in the 2006 National Health and Nutrition Survey were used to measure the serum concentrations of s-ferritin, soluble-transferrin-receptor (s-TfR), zinc, copper, and magnesium. Results. The prevalence of s-ferritin≤12ug/L was 18.1 and 3.6% while s-TfR>6mg/L was 9.5 and 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 30 publications
0
35
1
1
Order By: Relevance
“…To be included in the analysis, each report had to present the prevalence of anemia based on low hemoglobin levels as well as IDA (defined using low serum ferritin and low hemoglobin), where ideally, ferritin was adjusted for inflammation. The reported inflammation adjustment of included surveys was made by one of the following methods: (a) the approach proposed by Thurnham [15; 4-stage adjustment model: elevated C- reactive protein (CRP) only; both CRP and alpha-1-acid glycoprotein (AGP) elevated; or AGP elevated only]; (b) presenting IDA prevalence based on serum ferritin concentrations in a subsample without inflammation; (c) increasing the serum ferritin cut-off for ID to 20 μg/L for the whole study population (one survey [16]). In case IDA was not adjusted for inflammation by the authors, but the proportion of the population with elevated CRP or AGP was reported, IDA was adjusted applying an internal correction factor (see description below), and the survey was also included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…To be included in the analysis, each report had to present the prevalence of anemia based on low hemoglobin levels as well as IDA (defined using low serum ferritin and low hemoglobin), where ideally, ferritin was adjusted for inflammation. The reported inflammation adjustment of included surveys was made by one of the following methods: (a) the approach proposed by Thurnham [15; 4-stage adjustment model: elevated C- reactive protein (CRP) only; both CRP and alpha-1-acid glycoprotein (AGP) elevated; or AGP elevated only]; (b) presenting IDA prevalence based on serum ferritin concentrations in a subsample without inflammation; (c) increasing the serum ferritin cut-off for ID to 20 μg/L for the whole study population (one survey [16]). In case IDA was not adjusted for inflammation by the authors, but the proportion of the population with elevated CRP or AGP was reported, IDA was adjusted applying an internal correction factor (see description below), and the survey was also included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…26 Mexican and Ecuadorian women 12 to 49 years of age also had high rates of zinc deficiency (28% and 56%, respectively). 24,27 Mexico and Colombia have conducted two consecutive national surveys that collected information on serum zinc concentrations. In Mexican children between 6 months and 11 years of age, the prevalence of zinc deficiency was 25 The only country with available national data on dietary intake of zinc (by 24-hour recall) was Argentina.…”
Section: Prevalence Of Zinc Deficiency In Latin America and The Caribmentioning
confidence: 99%
“…The challenge is to have better ways to detect marginal copper deficiency. Further, there are selected populations where dietary copper is not so abundant, in which the prevalence of uncomplicated copper deficiency is significant …”
Section: Induction Of Copper Deficiencymentioning
confidence: 99%